The CIPP Model for Curriculum Evaluation in Islamic Education: A Comprehensive Literature Review - Aristya, Septian; Zurqoni; Khojir (Al-Hayat: Journal of Islamic Education, 2026)
This study aims to analyse how the CIPP (Context, Input, Process, Product) evaluation model can address existing barriers and improve the quality of Islamic Religious Education (IRE) curriculum amid globalisation challenges that cause moral degradation among younger generations. This research employs a library research method using content analysis to review scholarly literature from Scopus and other databases systematically. The CIPP evaluation framework developed by Stufflebeam was utilised to synthesise findings on curriculum evaluation in Islamic education contexts. The review reveals three key findings. First, context evaluation shows that successful IRE curricula must align educational objectives with national standards (UU Sisdiknas No. 20/2003) and Islamic educational philosophy while addressing contemporary moral challenges. Second, input and process evaluation identifies critical implementation factors, including teacher pedagogical competencies, student learning readiness, resource adequacy, and effectiveness of innovative strategies such as Project-Based Learning and cooperative learning. Third, product evaluation confirms that comprehensive outcome assessment must encompass cognitive achievement, character development, and religious competencies to fully measure curriculum effectiveness. This study is limited to literature-based analysis and requires empirical validation across diverse Indonesian Islamic educational settings. This research contributes by providing a systematic synthesis of CIPP model applications in IRE curriculum evaluation, offering practical recommendations for educators and policymakers to develop more effective, responsive Islamic education curricula that address contemporary challenges while maintaining Islamic educational principles.